Tracer Study on the Profile and Employability of Bachelor of Science: A Case Study of Food Service Management Graduates of Camarines Sur Polytechnic Colleges - Lagatic, Jenny N.; Ramos, Monique P.; Serrano, Edelyn B. (Journal of Organizational and Human Resource Development Strategies, 2024)
This study examines the profile and employability of Bachelor of Science in Food Service Management (BSFSM) graduates from Camarines Sur Polytechnic Colleges (CSPC) across three batches (2018–2019, 2019–2020, and 2020–2021). Employing a descriptive survey approach, the study utilized a Google Form questionnaire to collect data from a sample of 168 graduates, selected using Slovin's formula. The research explored the graduates' personal, professional, and employment profiles and their reasons for job retention, acceptance of unrelated jobs, and unemployment. Employer assessments of the graduates' job performance were also analyzed. Key findings reveal the employability trends of BSFSM graduates and the challenges they faced, particularly in light of the economic disruptions caused by the COVID-19 pandemic. Statistical tools were used to interpret the data, including percentage calculations and weighted mean. The study underscores the importance of aligning curriculum programs with industry demands to enhance graduate outcomes. Recommendations are provided to improve the employability of BSFSM graduates and address identified gaps.